Analisis Pelaksanaan Program Kerja Karang Taruna Di Desa Sedang Kecamatan Suek Tapeh Kabupaten Banyuasin - Nurjanah, Nurjanah; Mahriadi, Nopriawan (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM), Sekolah Tinggi Ilmu Sosial dan Ilmu Politik (STISIPOL) Candradimuka Palembang, 2021)
The research with the title Analysis of the Implementation of Youth Organization Work Program in Medium Villages, Suek Tapeh District, Banyuasin Regency. that the implementation of the youth organization's work program in development has not been optimal and there is a lack of attention and motivation from the village government. aiming at knowing the youth organization's work program and knowing the factors that hamper the work implementation program of the youth organization. based on Damayanty 2012 the role of youth or the young generation as pillars, drivers and guardians of the path of reform and development is highly expected, the younger generation are adolescents who will later become sprouts of hope and capital for future nation-building. this study uses qualitative descriptive analysis techniques with evaluative methods, qualitative methodology is a research procedure that produces descriptive data in the form of written and spoken words from people and observed behavior. the research informants were 9 respondents. results the development process brings the participation of village community leaders and organizations for implementing youth organizations in development, indicating that the role of karang taruna has a very important role in the ongoing process of infrastructure development, the efforts of karang taruna in development, namely through coordination in planning and submitting development proposals. Village office and coordinations of land provision for devlepment and supervision of development in the cummunity feeals the (responsivness) of the vellage apparatus to commonity compalints.